Cognitive impairment among alcohol treatment service users in South Wales: an exploratory examination of typologies of behaviour, impairment, and service attendance - Davies, Nyle H.; Lewis, Julia; John, Bev; Quelch, Darren; Roderique-Davies, Gareth (Frontiers in Psychiatry, 2024)
Introduction Alcohol dependence is a global issue with many negative consequences, including alcohol-related brain damage (ARBD). Assessment of the sociodemographic and cognitive characteristics of individuals with confirmed or suspected ARBD presenting to alcohol services warrants further investigation. Methods This study retrospectively examined rates of cognitive impairment using Montreal Cognitive Assessment (MoCA) data from 300 adults who visited three alcohol support services. We demonstrate that 55.3% of the sample had significant levels of cognitive impairment. Females’ cognitive performance was disproportionately negatively affected by historical alcohol use relative to males. Results The analysis identified four categories of participants, and the majority had a long history (+10 years) of alcohol use and were still actively drinking. Those taking part in active treatment for ARBD or practising abstinence demonstrated lower levels of cognitive impairment. Additionally, prior access to specialised ARBD care was associated with higher MoCA scores. Discussion This research has identified a range of key service engagement, sociodemographic and cognitive characteristics that could be used to optimise support for those with alcohol dependence, whilst also highlighting some critical questions to be addressed in future research.